PENGARUH MODEL PEMBELAJARAN ADVANCE ORGANIZER DENGAN MEDIA YOUTUBE TERHADAP PEMAHAMAN MATERI SEJARAH PESERTA DIDIK KELAS XI SMA - Rismatul Hakimah; Corry Liana (Prabayaksa: Journal of History Education, 2026)
Students' understanding of history remains suboptimal because learning is still dominated by conventional question-and-answer methods that fail to present historical events chronologically and interconnectedly. This situation tends to lead students to develop fragmented understandings, thus making it difficult to connect concepts and historical events. Furthermore, the limited integration of technology into the learning process further emphasizes the need for learning models that create more meaningful learning experiences.. This study aims to examine  the effect of the Advance Organizer learning model combined with YouTube on the understanding of history material at grade 11 students at Ta'miriyah Senior High School in Surabaya. This study employed a quantitative approach using a pre-experimental design, specfically a one-shot case study, Inovolving 32 eleventh-grade students at Ta’miriyah Surabaya. Data collection techniques included tests, questionnaire,  observation, and documentation. Data analysis was conducted using prerequisite tests and simple linear regression. The results showed that the application of the Advance Organizer learning model combined with YouTube had a positive and significant effect on students' understanding of history material. The hypothesis testing results showed a significance value less than 0.05, thus accepting the alternative hypothesis, with an R-square value of 0.610. The application of the Advance Organizer model helps students connect new knowledge with their pre-existing knowledge structures, while YouTube facilitates the presentation of history material in a more concrete, engaging, and meaningful way. Therefore, integrating the Advance Organizer learning model with YouTube can be an effective alternative learning strategy for improving students' understanding of history material